2021
DOI: 10.1108/fs-01-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

Business adversity during the COVID-19 crisis and beyond: the way forward for small and medium enterprises in India

Abstract: Purpose The novel coronavirus (COVID-19) leaves Indian business teetering on the edge of survival. This paper aims to set out to assess the impact of the pandemic shocks on the small and medium business segments in India. The research also explores the strategies that potentially take the segments back to recovery and growth. Design/methodology/approach The findings draw on the perspectives of academic and business people, and the authors use linear and nonlinear regression modelling under three recovery sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…As India is an emerging market, Covid-19 severely impacted most small businesses, which was unprepared for this unexpected crisis. The pandemic has triggered new and irreversible changes for small businesses (Nair, 2021). Government-imposed lockdowns during the pandemic, with restrictions on public gatherings, movement of people and travel, severely affected India's foodservice businesses.…”
Section: Introductionmentioning
confidence: 99%
“…As India is an emerging market, Covid-19 severely impacted most small businesses, which was unprepared for this unexpected crisis. The pandemic has triggered new and irreversible changes for small businesses (Nair, 2021). Government-imposed lockdowns during the pandemic, with restrictions on public gatherings, movement of people and travel, severely affected India's foodservice businesses.…”
Section: Introductionmentioning
confidence: 99%
“…The second strand of literature has documented the effects of Covid-19 on firms. Several descriptive studies have shown that firms experienced severe distress in both developed ( Bloom, Bunn, Mizen, Smietanka, Thwaites, 2020 , Bloom, Fletcher, Yeh, 2021 , Torrès, Benzari, Fisch, Mukerjee, Swalhi, Thurik, 2022 ) and developing countries ( Shen, Fu, Pan, Yu, Chen, 2020 , Nair, 2021 , Nordhagen, Igbeka, Rowlands, Shine, Heneghan, Tench, 2021 ). Besides examining firms’ outcomes in the post-lockdown period, we also explore the impact in a recovery phase two quarters after the lockdown ended and find that firms recovered in this later phase.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the impacts on small and medium enterprises (SMEs) are greater compared to large multinational companies (De Massis and Rondi, 2020; Ofori-Boateng et al. , 2022; Nair, 2022). Many countries around the world are experiencing a significant contraction of their economic activities (Soluk et al.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of COVID-19 disruptions on individuals, businesses, national economy and, more especially, on the way social and business interaction takes place has been enormous (Olatunde et al, 2022;Nair, 2022). Research has shown that the impacts on small and medium enterprises (SMEs) are greater compared to large multinational companies (De Massis and Rondi, 2020;Ofori-Boateng et al, 2022;Nair, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation